PARENTS’ LANGUAGE ATTITUDES TOWARDS LANGUAGES AND MAINTENANCE OF HERITAGE LANGUAGE - Sugiyanta (Dialectical Literature and Educational Journal, 2020)
This current research is to explore parents’ language attitudes towards languages and maintenance of heritage language and to find out the efforts of maintaining heritage language and its supporting and inhibiting factors. In this research, a questionnaire and semi-structured interview were employed to collect data. There were 62 respondents, consisting of 37 males and 25 females coming from eleven provinces in Indonesia. Questionnaires were distributed to the respondents by both electronic and direct systems. Respondents were asked to fill in the questionnaires. Interviews were conducted to some respondents. The findings of this current research reveal that most parents show positive attitudes towards languages and the maintenance of heritage language. The results also indicate that there were some factors supporting the maintenance of heritage language, including parents’ attitudes and roles, community, school, family, daily practices, and culture. In addition, there were a number of factors inhibiting to the maintenance of heritage language such as parents’ attitudes and roles, community, school, family, external culture, and technological advancements. In terms of the efforts to maintain the heritage language, the results show that the language should be taught in the families and at schools, and should be used for social interactions and in traditional and ceremonial events.